2017
DOI: 10.1038/s41598-017-16593-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones derivatives reduce proliferation and induce cell death and DNA damage in ovarian cancer

Abstract: Ovarian cancer is a highly aggressive disease and novel treatments are required. Thyroid hormones binding to αvβ3 integrin produced growth-promoting activities in ovarian cancer and we hypothesized that natural thyroid hormone derivatives may antagonize these actions. The effect of three antagonists, tetraiodoacetic acid (tetrac), triiodothyroacetic acid (triac) and 3-iodothyronamine (T1AM), on cell proliferation, cell death and DNA damage was studied in two ovarian cancer cell lines (OVCAR3 and A2780), normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…3-T 1 AM is a potential therapeutic agent for suppressing UM expansion as already indicated in other studies demonstrating that this thyroid hormone metabolite reduces cancer cell growth and viability (Rogowski et al, 2017 ; Shinderman-Maman et al, 2017 ). In UM cells, modulation of their metastatic activity appears to include changes in TRPV1 activity induced by TRPM8 and possibly CB1.…”
Section: Discussionmentioning
confidence: 78%
“…3-T 1 AM is a potential therapeutic agent for suppressing UM expansion as already indicated in other studies demonstrating that this thyroid hormone metabolite reduces cancer cell growth and viability (Rogowski et al, 2017 ; Shinderman-Maman et al, 2017 ). In UM cells, modulation of their metastatic activity appears to include changes in TRPV1 activity induced by TRPM8 and possibly CB1.…”
Section: Discussionmentioning
confidence: 78%
“…The three antagonists, tetraiodoacetic acid (tetrac), triiodothyroacetic acid (triac) and 3-iodothyronamine (T1AM) inhibited cell proliferation and induced cell death and DNA damage in the two ovarian cancer cell lines (OVCAR3 and A2780). Therefore, they concluded that the cytotoxic potential of thyroid hormone derivatives, tetrac, triac and T1AM, in ovarian cancer might provide a much-needed novel therapeutic approach (Shinderman-Maman et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Differently from metabolism-related diseases, much less is known about the effects of T1AM on liver carcinogenesis and neoplastic hepatocytes. Only few papers have investigated the effect of T1AM on cancer cells ( 113 , 114 ). In a recent paper it was found that micromolar doses of T1AM and its structural analog SG-2, are able to reduce viability and growth rate of the liver cancer cell line HepG2 and the breast cell line MCF7 ( 114 ) The exact mechanism by which T1AM altered cell viability and growth rate of these cancer cells is not entirely clear.…”
Section: T1am and Liver Cancermentioning
confidence: 99%